Environment-friendly moisture-cured polyurethane hot melt adhesive, preparation process and application thereof
Patent Information
- Application Number
- CN202611253573.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]根据以上现有技术中的不足,本发明的目的是提供一种环保型湿气固化聚氨酯热熔胶,通过多元醇的复配与功能化纳米填料的协同作用,在胶层内部构建了缓聚-窗口期排泡-室温固定协同机制,有效解决了传统聚氨酯热熔胶深层固化困难及界面气泡残留的问题
(1)本发明利用腰果酚基-MDI预加合物中腰果酚长链烷基的界面疏水屏蔽效应与保留酚羟基的反应滞后微观竞争效应,在湿气固化过程中缓冲表层交联反应速率峰值,避免表层因NCO基团瞬间暴聚而形成致密聚脲封闭层,为外部湿气向胶层深部的持续渗透保留时间窗口与微观扩散通道。适用于高分子防水卷材等致密基材的搭接粘接——即使在湿气仅能从胶层边缘缓慢渗透的闭气环境下,仍能实现胶层的深层透彻固化。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane adhesive technology, specifically to environmentally friendly moisture-curing polyurethane hot melt adhesives, their preparation process, and applications. Background Technology
[0002] Moisture-curing polyurethane hot melt adhesive (PUR hot melt adhesive) combines the advantages of high initial tack and easy application of hot melt adhesives with the high strength, high and low temperature resistance, and solvent resistance of reactive polyurethane adhesives. Its curing mechanism utilizes the reaction of terminal isocyanate groups (-NCO) with moisture in the air or on the substrate surface to generate urea bonds and produce CO2, thereby cross-linking and curing to form a three-dimensional network structure. PUR hot melt adhesive is widely used in furniture, building materials, automotive interiors, electronic assembly, and waterproof membrane construction.
[0003] However, existing PUR hot melt adhesives still have prominent problems when applied in thick layers or on dense substrates, such as premature skinning of the surface leading to difficulties in deep curing, and CO2 bubbles causing defects in the adhesive layer.
[0004] Several patent applications have explored solutions to the aforementioned problems. Chinese patent application CN111040715A, published on April 21, 2020, discloses a single-component reactive polyurethane hot melt adhesive. It introduces alkoxy groups through isocyanate-based propyltriethoxysilane, replacing isocyanate-based moisture curing with alkoxy-based moisture curing, thus avoiding CO2 generation at the source. However, this solution does not address the difficulty of moisture penetration during thick-layer application. Chinese invention patents CN115160969A, published on October 11, 2022, and CN115124964A, published on September 30, 2022, respectively, use zeolite molecular sieves and porous powders to adsorb CO2 or act as moisture channels to accelerate curing. However, both solutions use hydrophilic porous materials, which are prone to excessive moisture adsorption in the early stages of application, potentially exacerbating surface skinning and offering limited improvement for thick-layer curing. Chinese invention patents CN116333663A and CN116333664A, published on June 27, 2023, disclose carbon dioxide-based reactive polyurethane hot melt adhesives. These utilize carbon dioxide-based polyols to achieve low-carbon and environmentally friendly properties, but do not address the synergistic control of surface skin formation and deep curing during thick-layer application. Chinese patent application CN116536019A, published on August 4, 2023, discloses a high initial tack, high-strength moisture-curing reactive polyurethane hot melt adhesive. This adhesive uses a blend of polyester polyol and carbon dioxide-based polycarbonate polyol, achieving high initial tack strength without the need for additional tackifying resins. However, it still does not solve the synergistic problem of thick-layer curing and bubble suppression. Chinese patent application CN117701217A, published on March 15, 2024, discloses a bio-based moisture-curing polyurethane hot melt adhesive, which uses cashew phenol-based polyether polyol and bio-based polyester polyol in combination. However, the cashew phenol-based polyol was not pre-treated and its phenolic hydroxyl group reaction characteristics were not fully utilized.
[0005] In summary, there is currently a lack of an environmentally friendly PUR hot melt adhesive that can simultaneously solve the problems of premature skinning on the surface, difficulty in deep curing, and CO2 bubble defects during thick-layer application. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide an environmentally friendly moisture-curing polyurethane hot melt adhesive. Through the synergistic effect of polyol compounding and functionalized nanofillers, a synergistic mechanism of slow polymerization-window period defoaming-room temperature fixation is constructed inside the adhesive layer, which effectively solves the problems of difficult deep curing and residual interface bubbles in traditional polyurethane hot melt adhesives.
[0007] The purpose of this invention is to provide an environmentally friendly moisture-curing polyurethane hot melt adhesive preparation process. By controlling the temperature to avoid the crystallization zone and introducing a thermal stability promoter, the uniformity of adhesive dispersion and application stability are ensured, making it suitable for continuous industrial production.
[0008] This invention is achieved using the following technical solution: The first objective of this invention is to provide an environmentally friendly moisture-curing polyurethane hot melt adhesive, the technical solution of which is as follows: An environmentally friendly moisture-curing polyurethane hot melt adhesive comprises the following raw material components in parts by weight: CO2-based polypropylene carbonate diol: 25-45 parts; Crystalline polyester polyols: 10-25 parts; Cashew phenol polyol-diphenylmethane diisocyanate pre-reaction adduct: 5-15 parts; Diphenylmethane diisocyanate (MDI): 5-12 parts; Magnesium stearate surface-modified nano-magnesium oxide: 2-8 parts; Environmentally friendly catalyst: 0.05~0.3 parts; Moisture curing accelerator: 0.01~0.1 parts; Antioxidant: 0.1~0.5 parts; Silane coupling agent: 0.5~2 parts.
[0009] The above formula and parameter range are explained as follows: CO2-based polypropylene carbonate diol: As the main resin, it not only imparts good cohesive strength to the adhesive layer, but also possesses low-carbon and environmentally friendly properties due to the large number of carbonate bonds derived from CO2 in its structure. If the amount used is less than 25 parts, the cohesive strength and environmental benefits of the adhesive layer will be insufficient; if it is more than 45 parts, the strong polarity of the carbonate bonds in its molecular chain will lead to excessively high melt viscosity of the system, which is not conducive to sizing and wetting of the substrate.
[0010] Crystalline polyester polyols: Primarily used to provide initial tack for PUR hot melt adhesives. They crystallize and solidify rapidly upon cooling, enabling quick positioning. If the amount used is less than 10 parts, the initial tack is insufficient, easily leading to substrate displacement after bonding; if it is more than 25 parts, the system crystallizes too quickly, resulting in a short open time, reduced operational tolerance, and a brittle adhesive layer after curing.
[0011] The pre-reaction adduct of cashew nut polyol and diphenylmethane diisocyanate (MDI) is prepared by pre-reaction of cashew nut polyol and MDI at a molar ratio of NCO / side chain secondary hydroxyl groups of 1.8~2.5:1 and a temperature of 60~70℃. The pre-reaction conditions are mild and mainly allow MDI to react with the aliphatic secondary hydroxyl groups in the side chain of the cashew nut polyol molecule to form a terminal NCO prepolymer containing a hydrophobic long-chain alkyl backbone of cashew nut. The free NCO mass fraction of the obtained pre-reaction adduct is controlled at 3.0~6.0 wt%.
[0012] The mechanism of this pre-reaction adduct is as follows: the reaction between the isocyanate group and the hydroxyl compound is a nucleophilic addition process, and the reaction rate is mainly determined by the nucleophilicity of the nucleophile. The lone pair of electrons on the oxygen atom of the phenolic hydroxyl group in the cashew phenol molecule undergoes a conjugated delocalization effect with the benzene ring, reducing its nucleophilicity; while the oxygen atom of the aliphatic secondary hydroxyl group in the side chain is not conjugated and has a much stronger nucleophilicity than the phenolic hydroxyl group. Therefore, under pre-reaction conditions without a strong basic catalyst (the pre-reaction is carried out before the addition of DBU), MDI preferentially consumes the aliphatic secondary hydroxyl group in the side chain, generating a terminal NCO prepolymer containing a hydrophobic long-chain alkyl skeleton of cashew phenol (containing 15 carbon atoms) and retaining the low-activity phenolic hydroxyl group.
[0013] During the subsequent moisture coating and curing process, the introduction of this pre-adduct played a dual regulatory role of "interfacial hydrophobic shielding" and "reaction hysteresis microscopic competition": On the one hand, the long-chain alkyl group (C) in the cashew phenol structure 15 H 31 This endows the system with strong local hydrophobicity, forming low surface energy hydrophobic micro-regions on and near the surface of the adhesive layer. This moderately blocks the instantaneous excessive intrusion of environmental moisture into the adhesive layer surface, and avoids the explosive polymerization reaction between surface NCO groups and water from the perspective of physical diffusion. On the other hand, the retained low-activity phenolic hydroxyl groups and the trace amounts of infiltrated water form a delayed competition for NCO groups—although the nucleophilicity of phenolic hydroxyl groups is lower than that of water molecules, they are present at the polymer chain ends, and at local concentrations, they can effectively compete with and consume NCO groups, thus greatly buffering the initial peak rate of the surface NCO-H2O reaction. This "delayed competition" allows the surface curing reaction to proceed in a gentler manner, avoiding the formation of a dense polyurea sealing layer.
[0014] The aforementioned "hydrophobic shielding" and "hysteresis competition" work synergistically in the spatiotemporal dimension: hydrophobic shielding delays the onset time of moisture intrusion, while hysteresis competition reduces the intensity of the reaction after moisture intrusion. This dual spatiotemporal regulation effectively prevents the instantaneous aggregation on the surface to form a dense polyurea sealing layer (skin), thus preserving a time window and microscopic diffusion channels for the continuous penetration of external moisture into the deeper layers of the adhesive (especially the interface of the dense substrate), achieving a smooth transition of the curing rate along the thickness direction of the adhesive layer.
[0015] Magnesium stearate surface-modified nano-magnesium oxide: Magnesium stearate was used to perform surface hydrophobic modification on nano-magnesium oxide. After modification with magnesium stearate, the surface of nano-magnesium oxide changed from hydrophilic to hydrophobic, exhibiting good dispersibility and compatibility in polyurethane melt, avoiding the aggregation of nanoparticles and excessive side reactions with NCO groups, and ensuring the storage stability of the colloid. In this system, the core functions of modified nano-magnesium oxide are: (1) as a hydrophobic nano-reinforcing filler, it is uniformly dispersed in the polymer network, playing a role in stress dispersion and physical reinforcement; (2) with its nanoscale and large specific surface area, it performs physical adsorption and surface chemical adsorption on the curing byproduct CO2 (the weak alkaline sites on the surface of nano-magnesium oxide can undergo surface chemical adsorption with CO2, fixing free CO2 on the particle surface), reducing the supersaturation of free CO2 inside the colloid, and inhibiting the nucleation and growth of bubble nuclei; (3) the weak alkaline sites on its surface can neutralize the trace acidic substances that may be generated in the system, which helps the chemical stability of the system. If the amount added is less than 2 parts, the nano-reinforcement and CO2 adsorption effects are insufficient, and the bubble defects cannot be effectively suppressed; if the amount added exceeds 8 parts, the percolation effect of inorganic nanoparticles will cause the viscosity of the hot melt adhesive to increase exponentially, resulting in loss of adhesive application properties.
[0016] The moisture curing accelerator is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). As a strong organic base (pKa≈13.8), DBU does not function as a traditional CO2 stoichiometric absorber, but rather regulates the curing process through the following pathways: ① The alkaline sites of DBU catalyze the reaction between NCO groups and trace amounts of water in the system, accelerating the CO2 generated by the NCO-H2O reaction in the early stages of curing. DBU preferentially catalyzes the NCO-water reaction during the high-temperature, low-viscosity window period after sizing, ensuring that most CO2 is generated and escapes while the colloid still has sufficient fluidity, thereby reducing the generation and accumulation of CO2 inside the colloid layer after cooling and setting. After entering the high-viscosity stage at room temperature, the remaining trace amounts of CO2 generated by the NCO-water reaction are fixed by the chemical adsorption of nano-MgO; ② DBU and the weakly alkaline sites on the surface of nano-MgO form a synergistic alkaline microenvironment, promoting the wet mineralization reaction of CO2 on the surface of nano-MgO (generating magnesium bicarbonate / magnesium carbonate), enhancing the chemical adsorption and fixation efficiency of CO2 by nano-MgO. DBU plays a catalytic and synergistic adsorption-promoting role at extremely low addition levels (0.01~0.1 parts by weight) in this invention, so its dosage is far lower than the stoichiometric amount of CO2 produced to produce an effect.
[0017] The mechanism of action of the environmentally friendly moisture-curing polyurethane hot melt adhesive of this invention is based on the synergistic effect of surface curing rate regulation and physical-chemical dual foam suppression mechanism. This hypothesis is based on the macroscopic manifestation of the synergistic effect of each component, but this invention is not limited to this specific mechanism: (1) Surface curing rate regulation: The cashew phenol polyol-MDI pre-additive contains both phenolic hydroxyl groups and aliphatic secondary hydroxyl groups. Due to the conjugation delocalization effect of the benzene ring, the lone pair electrons on the oxygen atom of the phenolic hydroxyl group conjugate with the benzene ring, reducing nucleophilicity; while the oxygen atoms of the aliphatic secondary hydroxyl group on the side chain are not conjugated, and their nucleophilicity is much stronger than that of the phenolic hydroxyl group. Therefore, during the moisture curing process, the aliphatic secondary hydroxyl group preferentially participates in the crosslinking reaction, while the reaction rate of the phenolic hydroxyl group is relatively lagging. The two-stage reaction characteristic of fast first and slow later effectively buffers the initial crosslinking rate of the adhesive layer surface, avoiding the formation of a sealed layer due to the instantaneous aggregation of NCO groups on the surface, and preserving a time window and microscopic channels for the continuous penetration of external moisture into the deep part of the adhesive layer. It should be noted that the delayed reaction of the phenolic hydroxyl group and the concentration gradient of moisture diffusion from the surface to the inner layer work together to determine that the curing rate transitions smoothly along the thickness direction of the adhesive layer, thereby improving the problem of insufficient deep curing caused by the instantaneous skinning of the surface layer in traditional PUR hot melt adhesives.
[0018] (2) Interface regulation and physical reinforcement of hydrophobic nanoparticles: Nano-magnesium oxide (water contact angle up to 131~138.4°) modified with magnesium stearate exhibits good nanoscale dispersion in polyurethane melt. Its hydrophobic surface can moderately reduce the excessive response of the adhesive layer surface to high humidity, avoiding uncontrolled surface reaction rate. At the same time, as a rigid nanofiller, the uniformly dispersed nano-magnesium oxide particles can effectively fill the free volume in the polymer network, playing a physical reinforcing role in stress dispersion and crack deflection, and improving the cohesive strength and shear resistance of the cured adhesive layer.
[0019] The second objective of this invention is to provide a preparation process for the above-mentioned environmentally friendly moisture-curing polyurethane hot melt adhesive, characterized by comprising the following steps: (a) CO2-based polypropylene carbonate diol and crystalline polyester polyol are added to the reactor in the specified ratio and dehydrated at 110~120℃ and vacuum degree ≤-0.095MPa for 2~3h until the moisture content is ≤300ppm; the dehydration temperature is programmed to avoid local overheating. (b) Cool to 70-80°C, add the pre-reaction adduct of cashew phenolic polyol and MDI and the remaining MDI monomer in one go or in steps, and carry out the prepolymerization reaction at 80-85°C for 1.5-2.5 h under nitrogen protection until the NCO content reaches the theoretical design value (calculated based on the total NCO / OH molar ratio of 1.8-2.2:1, the target NCO content is 2.0-4.0 wt%). (c) Cool down to 75~80℃, add bismuth neodecanoate catalyst, magnesium stearate surface-modified nano magnesium oxide, DBU, antioxidant and silane coupling agent, turn on the ultrasonic dispersion device (frequency 20~40kHz, power 100~300W) to assist mixing, dispersion time 15~30min, control the temperature not to exceed 80℃ during dispersion. (d) Continue vacuum degassing at 75~85℃ for 20~40min until no bubbles are visible in the colloid. Then discharge the material under nitrogen protection and fill it into a moisture-proof aluminum foil packaging tube for sealed storage.
[0020] Furthermore, to achieve efficient industrial production, the preparation process can be continuously completed in a twin-screw reactive extruder, with segmented temperature control in each reaction section. Pre-grinding surface-modified magnesium stearate nano-magnesium oxide with an inert carrier (such as epoxidized soybean oil or low molecular weight polypropylene glycol) to form a nano-masterbatch can further prevent dust emissions and improve its continuous feeding accuracy and dispersion uniformity in the extruder.
[0021] The application of the environmentally friendly moisture-curing polyurethane hot melt adhesive in the bonding and construction of waterproof membranes is characterized by the following steps: melting the hot melt adhesive at 100~130℃, applying it to the overlap area of the waterproof membrane or the base layer, bonding it to another waterproof membrane or base layer within the open time, then rolling it to compact it, and performing moisture curing under natural ambient humidity.
[0022] The waterproof membrane is selected from thermoplastic polyolefin (TPO) waterproof membrane, polyvinyl chloride (PVC) waterproof membrane, or ethylene propylene diene monomer (EPDM) waterproof membrane; the substrate is selected from cement concrete base, metal roof, or polyurethane / polystyrene insulation board.
[0023] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention utilizes the interfacial hydrophobic shielding effect of the long-chain alkyl group of cashew phenol in the cashew phenol-MDI pre-admixture and the microscopic competition effect of the reaction lag of the retained phenolic hydroxyl group to buffer the peak of the surface crosslinking reaction rate during the moisture curing process, avoiding the formation of a dense polyurea sealing layer on the surface due to the instantaneous aggregation of NCO groups. This preserves a time window and microscopic diffusion channel for the continuous penetration of external moisture into the deep part of the adhesive layer. It is suitable for the overlapping bonding of dense substrates such as polymer waterproof membranes—even in an airtight environment where moisture can only slowly penetrate from the edge of the adhesive layer, deep and thorough curing of the adhesive layer can still be achieved.
[0024] (2) This invention utilizes the physical adsorption and surface chemical adsorption of hydrophobic nano-magnesium oxide, combined with the catalytic promoting effect of DBU on the NCO-H2O reaction, to achieve effective control of CO2. During the high-temperature and low-viscosity window period after sizing, DBU preferentially catalyzes the reaction between NCO and trace amounts of water, allowing most of the CO2 to escape when the colloid has good fluidity; after cooling and setting, the residual CO2 is fixed by the chemical adsorption of nano-MgO. The two work synergistically, macroscopically resulting in a reduction in the porosity of the adhesive layer after curing, effectively avoiding the hidden danger of water channeling caused by air bubble defects in the bonding of waterproof membranes.
[0025] (3) The formulation of this invention uses a large amount of CO2-based polypropylene carbonate diol and bio-based cashew phenol derivatives, which reduces the dependence on traditional petrochemical-derived polyether / polyester. By modifying the surface of nano magnesium oxide with stearic acid, combined with the dehydration, low-temperature ultrasonic dispersion and masterbatch addition technology in the preparation process, the dark reaction phenomenon of active filler under high temperature storage is effectively suppressed, ensuring the storage stability of hot melt adhesive under sealed conditions. Moreover, the melt viscosity is moderate, the application is smooth, and the applicability is wide. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0027] This invention provides an environmentally friendly moisture-curing polyurethane (PUR) hot melt adhesive, aiming to solve the technical problems of premature surface skinning, difficulty in deep curing, and stress concentration caused by internal carbon dioxide (CO2) foaming in existing PUR hot melt adhesives when applying thick layers or bonding dense substrates. To achieve the above objectives, this invention constructs a mechanism within the system that delays skinning, captures carbon and generates water, and promotes deep curing. The specific mechanism is as follows: (1) Design and functional considerations of the cashew phenol polyol-diphenylmethane diisocyanate (MDI) pre-reaction adduct: The cashew phenol molecule contains both a phenolic hydroxyl group and a secondary hydroxyl group on a long carbon chain. The reaction between the isocyanate group and the hydroxyl compound follows a nucleophilic addition mechanism, with the reaction rate primarily determined by the nucleophilicity of the nucleophile. The lone pair electrons on the oxygen atom of the phenolic hydroxyl group undergo conjugation delocalization with the benzene ring, reducing nucleophilicity; the oxygen atom of the aliphatic secondary hydroxyl group on the side chain is not conjugated, resulting in a much stronger nucleophilicity than the phenolic hydroxyl group. Based on this, in the pre-reaction stage (60-70℃, and without strongly basic substances such as DBU in the system), MDI preferentially reacts with the aliphatic secondary hydroxyl group on the side chain to generate a terminal NCO prepolymer containing a hydrophobic long-chain alkyl skeleton of cashew phenol (containing 15 carbon atoms) and retaining the low-reactivity phenolic hydroxyl group.
[0028] The core function of this pre-adduct after its introduction into the system lies in exerting a dual regulatory effect of "interfacial hydrophobic shielding" and "reaction hysteresis microscopic competition": (a) Interfacial hydrophobic shielding effect: The long-chain alkyl groups (C) in the cashew phenol molecule 15 H 31 The alkyl group () is a strongly hydrophobic segment. When this structure is covalently integrated into the polyurethane prepolymer backbone, these nonpolar long-chain alkyl groups tend to accumulate and oriented on the surface and near-surface of the adhesive layer, forming low-surface-energy hydrophobic microregions. These hydrophobic microregions can moderately impede the instantaneous excessive intrusion of ambient moisture into the adhesive layer surface, reducing the initial moisture supply rate of the surface NCO-H2O reaction, thereby avoiding the explosive polymerization reaction caused by excessive moisture supply to the surface and creating conditions for subsequent gradient moisture penetration.
[0029] (b) Reaction hysteresis micro-competitive effect: The retained low-activity phenolic hydroxyl groups (affected by the conjugation delocalization effect of the benzene ring, with nucleophilicity lower than that of water molecules) form a slow competition with the trace amounts of infiltrated water for NCO groups. Although the reaction rate of a single phenolic hydroxyl group with NCO is lower than that of a single water molecule with NCO, the phenolic hydroxyl groups are covalently linked to the polymer chain ends, resulting in a higher local effective concentration in the surface region of the adhesive layer. This "quantity advantage" allows it to consume a considerable proportion of NCO groups in the competition, thus effectively buffering the initial peak rate of the NCO-H2O reaction. This hysteresis competition allows the surface curing reaction to proceed in a more moderate manner.
[0030] The synergistic effect of the two effects described above is manifested in the following ways: within the limited space of the adhesive layer surface, "hydrophobic shielding" reduces the intrusion flux of moisture through physical barriers, while "hysteresis competition" reduces the peak intensity of the reaction through chemical consumption. The combined effect of these two factors allows the surface NCO-H2O reaction to initiate at a low initial rate and progress smoothly, thus preventing the instantaneous formation of a dense polyurea sealing layer (skin). This preserves a time window and microscopic diffusion channels for the continuous penetration of external moisture into the deeper layers of the adhesive layer. As the curing reaction progresses into the deeper layers, the moisture concentration gradient drives the moisture to gradually diffuse inward, and the cross-linking reaction is completed sequentially from the surface to the interior, ultimately achieving full curing of the entire adhesive layer.
[0031] It should be noted that the realization of the above-mentioned dual regulation effect depends on the process sequence of steps (b) and (c) - that is, the pre-reaction of cashew phenolic polyol with MDI is completed before the addition of DBU. This process sequence ensures that the phenolic hydroxyl groups will not be activated by strong alkaline substances during the pre-reaction stage, thus preventing the reaction selectivity from being reversed.
[0032] (2) Regarding the synergistic mechanism between nano-magnesium oxide and moisture curing accelerator: The system incorporates magnesium stearate-modified nano-magnesium oxide (particle size approximately 30-80 nm). The magnesium stearate surface modification treatment has the following effects: First, after modification with magnesium stearate, the surface of the nano-magnesium oxide changes from hydrophilic to hydrophobic. The organic long-chain coating effectively reduces the van der Waals forces between nanoparticles, preventing aggregation and ensuring nanoscale dispersion in the polyurethane matrix. Second, the surface hydrophobic treatment reduces the possibility of side reactions between the highly active hydroxyl groups on the nano-MgO surface and NCO groups during high-temperature storage, helping to extend the shelf life of the hot melt adhesive.
[0033] During the curing process after sizing, uniformly dispersed hydrophobic nano-MgO plays multiple roles: ① As a hydrophobic nano-reinforcing filler, it is uniformly dispersed in the polymer network, playing a role in stress dispersion and physical reinforcement; ② Due to its nanoscale size and large specific surface area, it physically adsorbs and chemically adsorbs CO2, a byproduct of curing (the weakly alkaline sites on the surface of nano-MgO can chemically adsorb CO2, fixing free CO2 on the particle surface), reducing the supersaturation of free CO2 inside the colloid and inhibiting the nucleation and growth of bubble nuclei; ③ Its weakly alkaline sites can neutralize trace amounts of acidic substances that may be generated in the system, contributing to the chemical stability of the system. DBU catalyzes the reaction of trace amounts of water with NCO, accelerating the early release of CO2.
[0034] (3) Regarding the thermodynamic matching of process temperatures: The system contains crystalline polyester polyols (such as poly(1,6-hexanediol adipate), whose melting point is approximately 60°C). During the ultrasonic dispersion step of the preparation process, if the temperature is below 70°C, the polyester segments are prone to microphase separation or even crystallization, leading to an exponential increase in melt viscosity and hindering the uniform dispersion of the nanoparticles. If the temperature is above 90°C, the risk of side reactions occurring in the terminal NCO groups increases. Therefore, controlling the ultrasonic dispersion temperature to 75–80°C ensures that the system is in a low-viscosity, homogeneous melt state, guaranteeing the hydrodynamic feasibility of physical blending.
[0035] Furthermore, the thermal stability of CO2-based polypropylene carbonate (PPC) during use primarily depends on the thermal decomposition temperature of the carbonate bonds in the molecular chain and the content of residual catalyst. Commercially available PPC products typically have thermal decomposition temperatures above 200°C, while the processing temperatures involved (prepolymerization 75-85°C, dispersion 75-80°C, and sizing 100-130°C) are all significantly lower than its obvious thermal decomposition temperature range. Simultaneously, the prepolymerization reaction is carried out under nitrogen protection, effectively reducing the risk of oxygen-induced side reactions under high-temperature conditions. Therefore, under these controlled process conditions, the structural integrity of PPC can be effectively maintained.
[0036] Raw material source: CO2-based polypropylene carbonate diol: purchased from relevant domestic manufacturers or cooperative manufacturers within the Chinese Academy of Sciences system, brand name PPC-3000, number average molecular weight Mn=3000, carbonate bond content approximately 42 wt%.
[0037] Crystalline polyester polyols: Poly(1,6-hexanediol adipate) diol (PHA, melting point approximately 60°C) and polycaprolactone diol (PCL, melting point approximately 60°C), both purchased from Wanhua Chemical Group Co., Ltd., with grades WHP-320 series and WHP-400 series respectively, or similar polyester polyol products.
[0038] Cashew nut polyols: Purchased from Cardolite, brand name NX-9011 or NX-9014, etc., cashew nut shell oil polyether polyols (hydroxyl value approximately 220~260 mgKOH / g), or similar products with equivalent hydroxyl values.
[0039] Diphenylmethane diisocyanate (MDI): Purchased from Wanhua Chemical Group Co., Ltd., brand name WANNATEMDI-50, purity ≥99.6%, liquid at room temperature.
[0040] Nano magnesium oxide (for surface modification): purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with an initial particle size of 50 nm and a purity of 99.9%.
[0041] Magnesium stearate (for surface modification): purchased from Shandong Xuchen Chemical Technology Co., Ltd., industrial grade, CAS 557-04-0, purity ≥99%, MgO content 6.5%~7.5%.
[0042] Anhydrous ethanol (for surface modification): purchased from Sinopharm Chemical Reagent Co., Ltd., analytical grade, purity ≥99.7%.
[0043] Bismuth neodecanoate (environmentally friendly catalyst): purchased from Vertellus (now part of Aurorium), USA, brand name Coscat83, an organic bismuth catalyst with an active bismuth content of approximately 16%.
[0044] DBU (Moisture Curing Accelerator): Purchased from Sinopharm Chemical Reagent Co., Ltd., purity 99%, CAS 6674-22-2.
[0045] Antioxidant 1010: Purchased from BASF, brand name Irganox 1010, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], CAS 6683-19-8, melting point 110~125℃.
[0046] Silane coupling agent KH-560: purchased from Evonik, brand name GLYMO, γ-glycidyl etheroxypropyltrimethoxysilane, CAS 2530-83-8.
[0047] Triethylenediamine (TEDA): Purchased from Evonik, brand name DABCO 33LV, a 33% dipropylene glycol solution of triethylenediamine.
[0048] Epoxidized soybean oil (for nano-masterbatch): Industrial grade, epoxy value ≥6.0%.
[0049] Polypropylene glycol (used in nano masterbatch): purchased from Jiangsu Dena Chemical Co., Ltd., grade PPG-2000, number average molecular weight 2000.
[0050] Polytetrahydrofuran ether diol (PTMEG-2000): Purchased from BASF, brand name PTMEG-2000, number average molecular weight 2000.
[0051] Ordinary nano magnesium oxide (unmodified): purchased from Shanghai Maclean Biochemical Technology Co., Ltd., hydrophilic, particle size 50 nm, purity 99.9%.
[0052] Hydrophilic nano silica: purchased from Henan Xunyu Chemical Co., Ltd., hydrophilic type, particle size 30~50 nm, SiO2 content ≥99.9%.
[0053] Zeolite molecular sieve: purchased from Sinopharm Chemical Reagent Co., Ltd., type 4A.
[0054] TPO waterproof membrane: purchased from Beijing Oriental Yuhong Waterproof Technology Co., Ltd., brand name PMT-3030 reinforced type, thickness 1.5 mm, width 2.0 m, conforming to standard GB 27789-2011.
[0055] Polyvinyl chloride (PVC) waterproof membrane: purchased from Keshun Waterproof Technology Co., Ltd., model H, thickness 1.2mm, width 2.0m, conforming to standard GB 12952-2011 "Polyvinyl chloride (PVC) waterproof membrane".
[0056] EPDM rubber waterproof membrane: purchased from Keshun Waterproof Technology Co., Ltd. or similar professional manufacturers, 1.5mm thick, 1.2m wide, conforming to standard GB / T 18173.1 "Polymer Waterproof Materials".
[0057] Cement concrete test blocks: prepared according to GB / T 50081 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", strength grade C30, size 150 mm × 150 mm × 150 mm.
[0058] Color steel sheet (metal roofing): Grade TDC51D+Z galvanized color-coated steel sheet, purchased from Baoshan Iron & Steel Co., Ltd. or regular steel market, surface polished and rust removed to Sa2.5 grade (or St3 grade).
[0059] Specifically, the preparation method of magnesium stearate surface-modified nano-magnesium oxide: Nano-sized magnesium oxide (initial particle size 50 nm, purity 99.9%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.) was placed in a vacuum oven and dried under vacuum at 120℃ for 4 hours for later use. Magnesium stearate, accounting for 3 wt% of the nano-sized magnesium oxide, was weighed and dissolved in anhydrous ethanol (the amount of anhydrous ethanol was 8 times the mass of the nano-sized magnesium oxide), and stirred in a 60℃ water bath until dissolved. The dried nano-sized magnesium oxide was added to the above magnesium stearate ethanol solution, and the reaction was carried out under constant temperature and stirring in a 75℃ water bath for 3 hours. During the reaction, ultrasonic dispersion was performed (frequency 40 kHz, power 200 W, 5 min each time, 10 min interval). After the reaction, the mixture was centrifuged, the precipitate was washed three times with anhydrous ethanol, dried in a 120℃ vacuum oven for 4 hours to constant weight, ground through a 200-mesh sieve, and sealed for later use.
[0060] Test method: (1) Melt viscosity determination The apparent viscosity of the hot melt adhesive samples was measured using a rotational viscometer (Brookfield DV2T) at a constant temperature of 120°C. The test rotor was SC4-27, and the rotation speed was set to 20 rpm. The viscosity value was recorded after the reading stabilized. Each sample was measured three times, and the average value was taken.
[0061] (2) Determination of opening hours The open time was determined using the finger-touch method, following ASTM D4497. Hot melt adhesive was melted at 120°C and then evenly spread onto a glass plate using a spatula to form a film approximately 0.5 mm thick. Timing began immediately after application. In a constant temperature and humidity environment of 25°C and 65% relative humidity, the surface of the adhesive film was lightly touched with a clean finger cot every 30 seconds. The point at which the adhesive threads stopped stringing and the film began to lose tackiness but was not yet fully cured was recorded as the end point of the open time. Each sample was measured three times, and the average value was taken.
[0062] (3) Deep curing depth test The adhesive was injected into a PTFE cylindrical mold with an inner diameter of 10 mm and a depth of 20 mm. It was then placed in a constant temperature and humidity chamber at 25°C and 65% relative humidity for 24 hours to cure. After curing, the mold was removed and cut open axially. The Shore A hardness tester or a miniature International Rubber Hardness Tester (IRHD) was used as the objective basis for judgment: hardness was measured every 1 mm from the air-exposed end inwards. The point where the hardness was first reached and subsequently three consecutive points showed a Shore A 30 (or IRHD 30) was recorded as the fully cured boundary. Simultaneously, the distance from this boundary to the surface was measured using calipers as the deep curing depth. Each sample was tested in triplicate, and the average value was taken.
[0063] (4) Internal porosity test A section (approximately 1 mm thick) of the colloid after the deep curing depth test was taken from the middle. The cross-section was photographed using a scanning electron microscope (SEM, accelerating voltage 5 kV) at a magnification of 200×. The porosity of the SEM images was calculated and statistically analyzed using ImageJ image analysis software. The statistical area was no less than 10 fields of view, covering different radial positions of the slice (center, half radius, and edge). The average value was taken as the porosity of the internal cross-section.
[0064] (5) Determination of storage viscosity growth rate The hot melt adhesive sample was sealed in an aluminum foil tube and stored in a 100°C oven for 7 days. After being removed and cooled to room temperature, the melt viscosity at 120°C was measured using the same method as described in (1). The viscosity growth rate was calculated using the following formula: Viscosity growth rate (%) = (Viscosity after heat storage - Initial viscosity) / Initial viscosity × 100%.
[0065] (6) Water contact angle test Molten hot melt adhesive was evenly applied onto a clean glass slide, controlling the film thickness to approximately 0.5 mm. The slide was then cured in a standard environment (25°C, 65% relative humidity) for 7 days to allow complete curing. Using an optical contact angle meter (such as a JC2000D or similar device), 3 μL of deionized water was dropped onto the cured film surface using a microsyringe at room temperature. After the water droplet stabilized for 5 seconds, the contact angle between the water droplet and the film surface was measured and recorded using the instrument's built-in software via the seated drop method. Five parallel tests were conducted on each sample in different areas, and the arithmetic mean was taken as the final water contact angle for that sample.
[0066] (7) CO2 Escape Measurement Take 50 g of each adhesive solution and place it in a sealed, temperature-controlled container (temperature 25℃, relative humidity 65%). Before testing, purge the top space of the container with high-purity nitrogen (≥99.99%) for 5 min to replace residual air, and record the initial gas volume reading as a blank. Connect a micro-flow meter (accuracy 0.1 mL) to the top of the container, and connect a gas sampling bag in series at the outlet. Read and record the cumulative gas volume at curing times of 2 h, 4 h, 8 h, 24 h, and 72 h. Simultaneously, use a portable infrared gas analyzer or gas chromatography (TCD detector, Porapak Q column) to confirm the CO2 composition of the gas in the sampling bag, and only include the volume confirmed to contain CO2 in the statistics. The final result is expressed as the cumulative CO2 escape volume (mL) per 100 g of adhesive solution after deducting the blank. Three samples were tested in parallel for each group, and the average value was taken.
[0067] (8) 180° peel strength test The test was conducted in accordance with the national standard GB / T 328.21-2007 "Test Methods for Waterproofing Membranes - Part 21: Peel Performance of Polymer Waterproofing Membranes". The peel rate was 100 mm / min. The maximum peel force (N / mm) during the peeling process was recorded. At the same time, the failure modes (membrane substrate failure / adhesive layer cohesive failure / interfacial adhesion failure) were observed and recorded.
[0068] (9) Peel strength retention rate test after immersion in alkaline water The peel strength test specimens prepared according to (8) were completely immersed in a saturated calcium hydroxide solution (Ca(OH)2, pH≈12.5, simulating the alkaline environment of cement concrete substrate) and soaked at room temperature (25℃) for 168 hours (7 days). After removal, the specimens were rinsed with deionized water and dried. After being left to air dry at room temperature for 2 hours, the peel strength was tested according to the method in (8), and the retention rate was calculated using the following formula: Retention rate (%) = Peel strength after alkaline water immersion / Peel strength under normal conditions × 100%.
[0069] (10) Isocyanate group (-NCO) content in the prepolymer: determined by the di-n-butylamine back titration method (refer to GB / T 12009.4-2016). Accurately weigh approximately 1-2 g (accurate to 0.0001 g) of the prepolymer sample and place it in a 250 mL stoppered conical flask. Add 25 mL of toluene-di-n-butylamine solution (toluene:di-n-butylamine = 100:25, volume ratio) to dissolve. After standing at room temperature for 30 min, add 50 mL of acetone and 5-6 drops of bromophenol blue indicator. Titrate with 0.1 mol / L hydrochloric acid standard solution until the blue color changes to yellow. Perform a blank test simultaneously. The NCO content is calculated using the following formula: NCO (wt%)=[(V0-V1)×C×42.02] / (m×1000)×100%; In the formula: V0 is the volume of hydrochloric acid consumed in the blank test (mL), V1 is the volume of hydrochloric acid consumed in the sample test (mL), C is the concentration of the hydrochloric acid standard solution (mol / L), m is the sample mass (g), and 42.02 is the molar mass of the NCO group (g / mol).
[0070] Example 1 (1) Material pretreatment: 35 parts by weight of CO2-based polypropylene carbonate diol and 18 parts by weight of poly(1,6-hexanediol adipate) diol were added to a reactor and dehydrated for 2 hours at 110°C and a vacuum of -0.098 MPa to reduce the moisture content to below 200 ppm. Cashew phenolic polyol and MDI were pre-reacted at 65°C at a molar ratio of NCO / side chain secondary hydroxyl groups of 2.0:1 to obtain a cashew phenolic polyol-MDI adduct containing terminal NCO and retaining phenolic hydroxyl groups.
[0071] (2) Two-stage reaction: The dehydrated diol system was cooled to 75°C, and 8 parts by weight of diphenylmethane diisocyanate (MDI) were added. The reaction was carried out under nitrogen protection for 1 hour to construct the main chain. Then, 10 parts by weight of the self-made cashew phenol polyol-MDI adduct were added, and the temperature was raised to 83°C to continue the reaction for 1.5 hours. After the prepolymerization reaction was completed, the NCO content was measured and the measured value was 3.2 wt%.
[0072] (3) Low-temperature dispersion and degassing: The reaction system was cooled and kept constant at 80°C. Then, 5 parts by weight of magnesium stearate surface-modified nano magnesium oxide, 0.15 parts by weight of bismuth neodecanoate, 0.05 parts by weight of DBU, 0.3 parts by weight of antioxidant 1010, and 1.2 parts by weight of silane coupling agent KH-560 were added sequentially. An ultrasonic generator with a power of 300W and a frequency of 30kHz was turned on to assist dispersion for 30 minutes. Finally, the bubbles were removed by vacuuming at 80°C, and the mixture was packaged in a nitrogen-filled sealed aluminum foil tube to obtain the hot melt adhesive of Example 1.
[0073] Example 2 The formulation was adjusted to: 25 parts by weight of CO2-based polypropylene carbonate diol, 10 parts by weight of poly(1,6-hexanediol adipate) diol, 5 parts by weight of cashew phenol-based polyol-MDI adduct, 5 parts by weight of MDI, 2 parts by weight of modified nano-magnesium oxide, 0.05 parts by weight of bismuth neodecanoate, 0.01 parts by weight of DBU, 0.1 parts by weight of antioxidant 1010, and 0.5 parts by weight of KH-560. The preparation process was the same as in Example 1. After the prepolymerization reaction was completed, a sample was taken to determine the NCO content, which was 3.8 wt%.
[0074] Example 3 The formulation was adjusted to: 45 parts by weight of CO2-based polypropylene carbonate diol, 25 parts by weight of poly(1,6-hexanediol adipate) diol, 15 parts by weight of cashew phenol-based polyol-MDI adduct, 12 parts by weight of MDI, 8 parts by weight of modified nano-magnesium oxide, 0.3 parts by weight of bismuth neodecanoate, 0.1 parts by weight of DBU, 0.5 parts by weight of antioxidant 1010, and 2.0 parts by weight of KH-560. The preparation process was the same as in Example 1. After the prepolymerization reaction was completed, a sample was taken to determine the NCO content, which was 2.4 wt%.
[0075] Example 4 The formulation and process of this embodiment are basically the same as those of Example 1, except that 18 parts by weight of poly(1,6-hexanediol adipate) diol are replaced with 18 parts by weight of polycaprolactone diol (PCL, Wanester 4000). After the prepolymerization reaction is completed, the NCO content is measured by sampling, and the measured value is 3.1 wt%.
[0076] Example 5 This embodiment employs a continuous extrusion process. The formulation ratio is the same as in Example 1. The parameters of the twin-screw reactive extruder are: screw diameter 50mm, length-to-diameter ratio L / D=48, screw speed 180rpm, and total feed rate 50kg / h. The polyol component and MDI component are metered and pumped into the main feed port of the twin-screw reactive extruder according to the ratio for prepolymerization in the front section. The front barrel temperature is set to 80℃ (zones 1-4). Surface-modified magnesium stearate nano-magnesium oxide is pre-mixed and ground with polypropylene glycol with a molecular weight of 2000 at a mass ratio of 40:60 to prepare a nano-masterbatch. This masterbatch is mixed with bismuth neodecanoate, DBU, antioxidant, and silane coupling agent, and then injected into the middle and rear sections of the extruder through the side feed port (middle and rear barrel temperature set at 78℃, zones 5-8), with a residence time of approximately 4 minutes to ensure uniform dispersion. A vacuum degassing port is provided at the end of the extruder, with a vacuum degree ≤-0.09MPa, to remove residual air bubbles. After the extrudate exits the die head, it is directly filled into moisture-proof aluminum foil packaging tubes and sealed under nitrogen protection to obtain the hot melt adhesive of Example 5. During continuous production, samples are taken every 30 minutes to test the NCO content and ensure batch-to-batch consistency. The NCO content was measured at the extruder outlet, and the measured value was 3.3 wt%.
[0077] Comparative Example 1 The formulation and process are the same as in Example 1, except that 10 parts by weight of cashew phenol-based polyol-MDI adduct are replaced with 10 parts by weight of conventional polytetrahydrofuran ether diol (PTMEG-2000), thus eliminating the phenolic hydroxyl sustained-release crosslinking mechanism of the cashew phenol structure.
[0078] Comparative Example 2 The formulation and process are the same as in Example 1, except that 5 parts by weight of magnesium stearate surface-modified nano magnesium oxide are completely removed from the system, thus the core carrier for CO2 adsorption and fixation and bubble suppression is missing.
[0079] Comparative Example 3 The formula and process are the same as in Example 1, except that: the surface-modified nano magnesium oxide of magnesium stearate is replaced with 5 parts by weight of ordinary nano magnesium oxide that has not undergone any modification treatment and is added directly.
[0080] Comparative Example 4 The formulation and process are the same as in Example 1, except that moisture curing accelerator (DBU) is completely removed from the system.
[0081] Comparative Example 5 The system uses a pure petrochemical base material system: 35 parts by weight of polytetrahydrofuran ether diol, 18 parts by weight of poly(1,6-hexanediol adipate) diol, 10 parts by weight of MDI, 0.15 parts by weight of bismuth neodecanoate, 0.3 parts by weight of antioxidant 1010, and 1.2 parts by weight of silane coupling agent KH-560. It contains no cashew nut shell polyol-MDI pre-reaction adduct, no modified nano-magnesium oxide, and no moisture curing accelerator DBU. The preparation process follows the same steps and parameters as in Example 1 (dehydration, prepolymerization, degassing, and filling).
[0082] Comparative Example 6 The formulation and process are the same as in Example 1, except that 0.05 parts by weight of DBU are replaced with an equal weight of polyurethane catalyst triethylenediamine (TEDA).
[0083] Comparative Example 7 The formulation and process are the same as in Example 1, except that 10 parts by weight of the cashew phenolic polyol-MDI pre-reaction adduct are replaced with 10 parts by weight of unreacted cashew phenolic polyol free monomer (i.e., the cashew phenolic polyol is directly blended with other components), while the remaining components and process remain unchanged. This comparative example is used to verify the necessity of introducing cashew phenolic polyol in the form of a pre-adduct.
[0084] Comparative Example 8A: The formula and process are the same as in Example 1, except that the amount of DBU added is 0.001 parts.
[0085] Comparative Example 8B: The formula and process are the same as in Example 1, except that the amount of DBU added is 0.5 parts.
[0086] Comparative Example 8C: The formula and process are the same as in Example 1, except that the amount of DBU added is 1.0 part.
[0087] Comparative Example 9A: The formulation and process are the same as in Example 1, except that the modified nano-MgO is replaced with hydrophilic nano-silica (particle size 30~50nm, in equal amounts).
[0088] Comparative Example 9B: The formulation and process are the same as in Example 1, except that the modified nano MgO is replaced with zeolite molecular sieve.
[0089] The test results of the products obtained in Examples 1-5 and Comparative Examples 1-9B are shown in Table 1.
[0090] Table 2 shows the cumulative volume data of CO2 gas released at different time periods in Example 1 and Comparative Examples 2, 4, and 5.
[0091] Table 3 shows the curing effect data of Example 1 and Comparative Example 5 under different adhesive application thicknesses.
[0092] Table 1: Product test results obtained from Examples 1-5 and Comparative Examples 1-9B
[0093] As shown in Table 1, compared with Comparative Example 5, the deep curing depth of Examples 1-5 increased to between 7.2 and 9.2 mm, and the interior was essentially pore-free. Comparative Example 1 lacked the differential reactivity regulation between the phenolic hydroxyl and aliphatic hydroxyl groups in the cashew phenol structure, resulting in a lack of slowing polymerization effect, leading to rapid surface crusting, blocking the penetration path of external moisture, and a sharp drop in curing depth to 3.5 mm. Comparative Example 2 lacked modified nano-magnesium oxide, and due to the lack of nano-surfaces and physical reinforcing phases for adsorbing CO2, bubbles could not be effectively suppressed and the adhesive layer strength was insufficient, resulting in a cross-sectional porosity of up to 8.5%, forming serious defects. Comparative Example 4 lacked DBU catalysis, and CO2 failed to be released in a concentrated manner within the window period, resulting in a porosity of 4.2%. In Comparative Example 6, replacing DBU with TEDA resulted in inferior deep curing and foam suppression effects compared to Example 1, indicating that DBU's role is irreplaceable. Although TEDA is a tertiary amine catalyst, it lacks the alkaline synergistic ability of the amidine group, failing to simultaneously achieve the dual functions of catalyzing the NCO-H2O reaction and promoting CO2 chemisorption on the surface of nano-MgO. In Comparative Example 7, cashew phenol polyol was directly added as a free monomer rather than as a pre-adduct, leading to increased system viscosity, shortened open time, and a deep curing depth of only 3.8 mm. This is because the free cashew phenol polyol, without pre-reaction control, rapidly participates in the reaction at the initial stage of curing, lacking a slowing effect, and instead causing premature surface closure due to the excessively rapid reaction. The gelation phenomenon in Comparative Example 3, conversely, confirms that surface hydrophobic modification of nano-magnesium oxide with magnesium stearate and control of low-temperature dispersion processes play a crucial role in ensuring product stability during storage. The series of Comparative Examples 8 revealed a clear U-shaped curve pattern in the effect of DBU on porosity. When the DBU addition is extremely low, the catalytic defoaming efficiency is insufficient, and the porosity reaches 3.5%; within a better range, the porosity is <0.5%; however, once excessive, the NCO-H2O reaction rate becomes extremely uncontrolled, and the generated CO2 is instantly overloaded, far exceeding the chemical adsorption limit of nano-MgO. This not only leads to violent internal foaming but also significantly shortens the open time to the point of being unusable. Comparative Example 9 further demonstrates the necessity of hydrophobic modification of stearic acid. Whether it is hydrophilic MgO, hydrophilic SiO2, or molecular sieves with physical porous adsorption, the hydrophilic surface excessively attracts water in the early stage of sizing, exacerbating premature surface crusting and deteriorating storage stability. Overall, the defoaming and deep curing effects are far inferior to those of hydrophobic nano-MgO.
[0094] Table 2: Cumulative volume data of CO2 gas released at different time periods in Example 1 and Comparative Examples 2, 4, and 5
[0095] As shown in Table 2, Example 1 exhibited a higher CO2 release rate in the early stages of curing compared to the comparative examples, demonstrating that the DBU successfully catalyzed the early reaction of moisture and NCO, and concentrated the exhaust gas. However, in the later stages of curing, the total amount of gas released in Example 1 hardly increased and remained extremely low, indicating that the residual trace amounts of CO2 were completely chemically adsorbed and fixed by the modified nano-MgO surface. In contrast, the comparative examples showed significant gas bulging in the later stages due to the slow, deep reaction and lack of exhaust outlets.
[0096] Table 3: Curing effect data of different adhesive application thicknesses in Example 1 and Comparative Example 5
[0097] Table 3 shows that the traditional comparative example can basically cure under a 1mm thin adhesive layer; however, as the adhesive thickness increases to 5mm, comparative example 5, due to the surface skinning effect, cannot allow moisture to penetrate, and the curing depth stagnates at 2.5mm, with internal air bubbles rising sharply. Example 1, even at a thickness of 5mm, can still cure completely and without foaming, proving that the present invention specifically solves the application problem in dense environments with thick adhesive.
[0098] Application Example 1: A surface-dried cement concrete sample block was used as the base layer. The hot melt adhesive prepared in Example 1 was melted at 120°C and then evenly applied to the concrete substrate using a scraper application method, with an application rate of 150 g / m². 2 During the open period, lay a 1.5mm thick TPO waterproof membrane (with corona-treated surface) flat on the adhesive layer and press it flat with a pressure roller to remove air. Cure at room temperature (25℃, 65% relative humidity) for 72 hours.
[0099] Application Example 2: Two 1.2mm thick PVC waterproof membrane sheets were selected and overlapped (overlap width 80mm). The hot melt adhesive of Example 5 (continuous extrusion type) was melted and continuously extruded into the overlap area, with an adhesive thickness of about 1.5mm. After closing, pressure was applied to bond them together, and they were cured under the same conditions for 72 hours.
[0100] Application Example 3: After grinding and rust removal, color steel plates and 1.5mm thick EPDM rubber waterproof membrane were selected. Hot melt adhesive from Example 1 was used, with the adhesive application rate adjusted to 120 g / m². 2 The remaining coating and curing processes are the same as in Application Example 1.
[0101] Application Comparative Example 1: The same TPO and concrete substrate as in Application Example 1 were used, but the adhesive was replaced with the adhesive prepared in Comparative Example 1.
[0102] Application Comparative Example 2: The same PVC overlapping process as in Application Example 2 was used, but the adhesive was replaced with the adhesive prepared in Comparative Example 2.
[0103] Application Comparative Example 3: Using the same TPO and concrete substrate as in Application Example 1, the adhesive was replaced with the adhesive prepared in Comparative Example 5.
[0104] Application Comparative Example 4: The same process as in Application Example 1 was used, except that the adhesive was replaced with the adhesive prepared in Comparative Example 7.
[0105] The test results of Application Examples 1-3 and Application Comparative Examples 1-4 in waterproof membranes are shown in Table 4.
[0106] Table 4: Test results of application examples 1-3 and comparative examples 1-4 in waterproof membranes
[0107] As shown in Table 4, polymer waterproof membranes (especially TPO and PVC) possess a dense waterproof and breathable barrier that blocks environmental moisture, making it extremely difficult for conventional PUR adhesives to achieve thorough cross-linking in the core area. The normal peel strength of Examples 1 and 2 both exceeded 3.5 N / mm, and the membrane substrate itself fractured under tension, indicating that the cohesive force and interfacial adhesion of the adhesive layer far exceeded the intrinsic strength of the polymer waterproof membrane. Furthermore, after a harsh alkaline water immersion test, due to the absence of pores in the adhesive layer, water molecules could not penetrate, resulting in a strength retention rate of over 90%, demonstrating good waterproof and weather-resistant reliability. In contrast, the loss of skin buffering or chemical defoaming can lead to a fluid-like or sponge-like pore stress concentration zone in the sandwich layer, increasing the risk of early delamination and leakage.
Claims
1. An environmentally friendly moisture-curing polyurethane hot melt adhesive, characterized in that, It contains the following raw material components in parts by weight: CO2-based polypropylene carbonate diol: 25-45 parts; Crystalline polyester polyols: 10-25 parts; Cashew phenol polyol-diphenylmethane diisocyanate pre-reaction adduct: 5-15 parts; Diphenylmethane diisocyanate: 5-12 parts; Magnesium stearate surface-modified nano-magnesium oxide: 2-8 parts; Environmentally friendly catalyst: 0.05~0.3 parts; Moisture curing accelerator: 0.01~0.1 parts; Antioxidant: 0.1~0.5 parts; Silane coupling agent: 0.5~2 parts.
2. The environmentally friendly moisture-curing polyurethane hot melt adhesive according to claim 1, characterized in that, The CO2-based polypropylene carbonate diol is copolymerized from CO2 and propylene oxide and treated to remove residual catalyst. The carbonate bond content in the molecule is 30-50 wt%, and the number average molecular weight Mn is 2500-3500. The crystalline polyester polyol is selected from one or more of poly(1,6-hexanediol adipate), poly(1,4-butanediol adipate), or polycaprolactone diol, and has a melting point of 50-70°C.
3. The environmentally friendly moisture-curing polyurethane hot melt adhesive according to claim 1, characterized in that, The pre-reaction adduct of cashew phenolic polyol and diphenylmethane diisocyanate is prepared by pre-reaction of cashew phenolic polyol and diphenylmethane diisocyanate at a molar ratio of NCO / secondary hydroxyl group of 1.8~2.5:1 and a temperature of 60~70℃. The free NCO mass fraction of the obtained pre-reaction adduct is controlled at 3.0~6.0 wt%.
4. The environmentally friendly moisture-curing polyurethane hot melt adhesive according to claim 1, characterized in that, The magnesium stearate-modified nano-magnesium oxide is prepared by dehydration condensation reaction of nano-magnesium oxide with a particle size of 30-80 nm and magnesium stearate accounting for 3-10% of the mass of nano-magnesium oxide in anhydrous ethanol at 70-80 °C; the surface of the modified nano-magnesium oxide changes from hydrophilic to hydrophobic.
5. The environmentally friendly moisture-curing polyurethane hot melt adhesive according to claim 1, characterized in that, The moisture curing accelerator is 1,8-diazabicyclo[5.4.0]undec-7-ene.
6. A preparation process for an environmentally friendly moisture-curing polyurethane hot melt adhesive as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (a) CO2-based polypropylene carbonate diol and crystalline polyester polyol are added to a reaction vessel in a certain ratio and dehydrated at 110~120℃ and vacuum degree ≤-0.095MPa for 2~3h until the moisture content is ≤300ppm. (b) Cool down to 70~80℃, add the pre-reaction adduct of cashew phenol polyol and diphenylmethane diisocyanate and the remaining diphenylmethane diisocyanate monomer in one go or in steps, and carry out the prepolymerization reaction at 80~85℃ for 1.5~2.5h under nitrogen protection until the NCO content reaches the theoretical design value. (c) Cool down to 75~80℃, add bismuth neodecanoate catalyst, magnesium stearate surface-modified nano magnesium oxide, moisture curing accelerator, antioxidant and silane coupling agent, turn on the ultrasonic dispersion device to assist mixing, disperse for 15~30min, and control the temperature not to exceed 80℃ during dispersion. (d) Continue vacuum degassing at 75~85℃ for 20~40min until no bubbles are visible in the colloid. Then discharge the material under nitrogen protection and fill it into a moisture-proof aluminum foil packaging tube for sealed storage.
7. The preparation process according to claim 6, characterized in that, The preparation process is completed continuously in a twin-screw reactive extruder; the temperature of each reaction section of the twin-screw reactive extruder is controlled in stages by jacketed heat transfer oil or electric heating; the ultrasonic assistance in step (c) has a frequency of 20~40kHz and a power of 100~300W.
8. The preparation process according to claim 6, characterized in that, In step (c), the magnesium stearate surface-modified nano magnesium oxide is prepared by grinding and dispersing with an inert carrier without NCO groups in advance to form a nano masterbatch with a nano magnesium oxide mass fraction of 30-50% before being added to the system; the inert carrier is selected from epoxidized soybean oil or polypropylene glycol with a number average molecular weight of 2000-4000.
9. The application of an environmentally friendly moisture-curing polyurethane hot melt adhesive as described in any one of claims 1 to 5 in the bonding and construction of waterproof membranes, characterized in that, The process includes the following steps: melting the hot melt adhesive at 100~130℃, applying it to the overlap area of the waterproof membrane or the base layer, bonding it to another waterproof membrane or base layer within the open time, then rolling it to compact it, and then performing moisture curing under natural ambient humidity.
10. The application according to claim 9, characterized in that, The waterproof membrane is selected from thermoplastic polyolefin waterproof membrane, polyvinyl chloride waterproof membrane, or EPDM rubber waterproof membrane; the substrate is selected from cement concrete base, metal roof, or polyurethane / polystyrene insulation board.
Citation Information
Patent Citations
Single-component reactive polyurethane hot melt adhesive and preparation method thereof
CN111040715A
Moisture-curable polyurethane hot melt adhesive as well as preparation method and application thereof
CN115124964A
Single-component moisture-curing reaction type PUR hot melt adhesive and preparation method thereof
CN115160969A
Carbon dioxide-based reactive polyurethane hot melt adhesive and preparation method thereof
CN116333663A
Dual-curable carbon dioxide-based reactive polyurethane hot melt adhesive and preparation method thereof
CN116333664A